3D nanostructured inkjet printed graphene via UV-pulsed laser irradiation enables paper-based electronics and electrochemical devices. Issue 35 (11th August 2016) - Das, Suprem R.; Nian, Qiong; Cargill, Allison A.; Hondred, John A.; Ding, Shaowei; Saei, Mojib; Cheng, Gary J.; Claussen, Jonathan C.
Abstract : Inkjet printed graphene is transformed into a 3D nanostructured, highly conductive flexible electrode via a pulsed-laser processing technique. Abstract : Emerging research on printed and flexible graphene-based electronics is beginning to show tremendous promise for a wide variety of fields including wearable sensors and thin film transistors. However, post-print annealing/reduction processes that are necessary to increase the electrical conductivity of the printed graphene degrade sensitive substrates ( e.g., paper) and are whole substrate processes that are unable to selectively anneal/reduce only the printed graphene—leaving sensitive device components exposed to damaging heat or chemicals. Herein a pulsed laser process is introduced that can selectively irradiate inkjet printed reduced graphene oxide (RGO) and subsequently improve the electrical conductivity ( R sheet ∼0.7 kΩ □ −1 ) of printed graphene above previously published reports. Furthermore, the laser process is capable of developing 3D petal-like graphene nanostructures from 2D planar printed graphene. These visible morphological changes display favorable electrochemical sensing characteristics—ferricyanide cyclic voltammetry with a redox peak separation (Δ E p ) ≈ 0.7 V as well as hydrogen peroxide (H2 O2 ) amperometry with a sensitivity of 3.32 μA mM −1 and a response time of <5 s. Thus this work paves the way for not only paper-based electronics with graphene circuits, it enables the creation of low-cost and disposable graphene-based electrochemical electrodes for myriad applications including sensors, biosensors, fuel cells, and theranostic devices.